Correlates of protection against influenza infection in humans—on the path to a universal vaccine? - Li, Chris Ka-fai; Rappuoli, Rino; Xu, Xiao-Ning (Current opinion in immunology, 2013)
•Influenza infection is prevented by protective antibodies.•Flu-specific T cells can reduce viral load and disease severity.•Stem region of HA and flu internal proteins (NP and M1) are highly conserved among influenza virus.•Boosting antibody and T cell responses against conserved regions of flu proteins may be critical. Influenza is an acute respiratory viral infection with high mutation rate and pandemic potential. Vaccination is an effective means of prevention and control of influenza, but the challenges of vaccine mismatches for the next influenza seasons and adequate global supply of influenza vaccines limit its effectiveness. Protective immunity in vaccination or natural infection is primarily mediated by antibody responses against surface proteins of influenza including haemagglutinin (HA) as the major neutralizing target, whereas strong T cell responses to internal viral proteins are associated with reduced disease severity. Recently, identification of broadly neutralizing antibodies against the conserved stem region of HA from influenza infected individuals has invigorated interest in development of a universal vaccine against different subtypes of influenza. Moreover, because of the cross-reactive nature of T cell recognition and more conserved internal antigens of influenza, strategies that boost memory T cell responses to these internal antigens may provide not only help for antibody-mediated protection but also limit the cell damage caused by viral infection directly. This is particularly important in acute infection with new pandemic viruses or antibody-escape variants where there are no pre-existing neutralizing antibodies. Here, we review the protective immune correlates against human influenza infection and discuss current status of universal influenza vaccine development.